Manajemen Pendidikan, Standar Pendidik, Tenaga Kependidikan, dan Mutu Pendidikan - Hidayati, Hidayati (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
Educational management in its strategic, managerial, and operational point of view determines the quality of education. Educational leadership - being the most important aspect of the educational management, together with the standard and human resources comprise the quality of education. The good quality of education is, therefore, determined by the leadership. It follows then that good performance of leadership brings about the standard as well as human resources of education. Effective leadership in education is thought to be able to realize these standard and resource, which further support or improve the quality of education. Consequently, strong commitment on the parts of the educational enterprise to realize the expected results is a must.Copyright © 2014 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v21i1.71